Research on Recognition of Deck Cars Based on Big Data Technology - Li, Jinsong (Transactions on Computer Science and Intelligent Systems Research, 2024)
With the increasing number of vehicles and the increasingly prominent traffic safety problems, deck cars have become a difficult problem that seriously affects social security and traffic order. Aiming at the problem of deck car recognition, this paper proposes a deck car recognition model based on big data technology. By collecting a large number of vehicle data, combining with deep learning and traditional machine learning methods, an effective recognition model of deck vehicles is designed and its performance is verified in experiments. The experimental results show that our model has achieved very high performance in accuracy, recall, precision and F1 score, and has good generalization ability. This study provides new ideas and methods for the research and practice in the field of deck car recognition, and has certain theoretical and application value.